Ice nucleation activity of agricultural soil dust aerosols from Mongolia, Argentina, and Germany. Issue 22 (17th November 2016) - Steinke, I.; Funk, R.; Busse, J.; Iturri, A.; Kirchen, S.; Leue, M.; Möhler, O.; Schwartz, T.; Schnaiter, M.; Sierau, B.; Toprak, E.; Ullrich, R.; et al.
Abstract: Soil dust particles emitted from agricultural areas contain considerable mass fractions of organic material. Also, soil dust particles may act as carriers for potentially ice‐active biological particles. In this work, we present ice nucleation experiments conducted in the Aerosol Interaction and Dynamics in the Atmosphere (AIDA) cloud chamber. We investigated the ice nucleation efficiency of four types of soil dust from different regions of the world. The results are expressed as ice nucleation active surface site (INAS) densities and presented for the immersion freezing and the deposition nucleation mode. For immersion freezing occurring at 254 K, samples from Argentina, China, and Germany show ice nucleation efficiencies which are by a factor of 10 higher than desert dusts. On average, the difference in ice nucleation efficiencies between agricultural and desert dusts becomes significantly smaller at temperatures below 247 K. In the deposition mode the soil dusts showed higher ice nucleation activity than Arizona Test Dust over a temperature range between 232 and 248 K and humidities RHice up to 125%. INAS densities varied between 10 9 and 10 11 m − 2 for these thermodynamic conditions. For one soil dust sample (Argentinian Soil), the effect of treatments with heat was investigated. Heat treatments (383 K) did not affect the ice nucleation efficiency observed at 249 K. This finding presumably excludes proteinaceous ice‐nucleating entities as the only source of the increased ice nucleation efficiency. Key Points: Aerosols from four agricultural areas are more ice active than desert dusts Soil dust particles are good candidates for ice nucleation in warm clouds The role of primary biological particles in soil dust agglomerates with regard to the observed ice nucleation properties remains unclear